The growing challenge of the extreme right - Kumar Ramakrishna (2021)
Two decades since the 11 September attacks in the United States, a new trend has emerged in political and religiously-inspired violence in the broad form of Extreme Right Movements, at times fomenting hate crimes, violence and even terrorism.